Strengthening mortgage-backed securitization in the Philippines the role of the National Housing Mortgage Finance Corporation (NHMFC) - Dulay, Daisy S.; Ballesteros, Marife M. (2013)
With stricter risk management for banks and financial institutions and the need to address the housing gap of nearly three million units annually, strategies that will provide long-term funds and expand home finance specifically to the low- and moderate-income households are essential to ensure the sustainability of housing finance. One potential option is to develop mortgage-backed securitization to strengthen the private securities market and the capital market.

This Policy Note discusses the role of the National Home Mortgage Finance Corporation (NHMFC) in developing securitization in the country. The NHMFC is the major government corporation created to operate as a secondary mortgage institution but this mandate has not been fully implemented in the past 30 years as NHMFC operations have been diverted to loan origination. With the approval of the Securitization Act of 2004 and improvements in the financial sector, opportunities to engage in securitization have opened up. The NHMFC has taken this opportunity to undertake securitization as a strategy to expand home finance.
Keywords: Mortgage-backed securities; National Housing Mortgage Finance Corporation